2011
DOI: 10.3109/02770903.2011.631243
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Asthma Control Criteria: Importance of Spirometry

Abstract: Asthma control ratings using GINA and CTS criteria are discordant in more than half of the patients deemed "in control" by at least one scale. Differences in the spirometry criterion threshold are primarily responsible for this discordance. Failure to include spirometry as part of the control index consistently overestimates asthma control and may underestimate future risk of exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…41 A study in primary care from Canada showed the importance of using a spirometer as part of the control index for patients from 6 years of age. 42 In the present study, only a minority of the children older than 6 years of age had ever undergone a spirometry test even though all the PHCs had access to a spirometer.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 62%
“…41 A study in primary care from Canada showed the importance of using a spirometer as part of the control index for patients from 6 years of age. 42 In the present study, only a minority of the children older than 6 years of age had ever undergone a spirometry test even though all the PHCs had access to a spirometer.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 62%
“…The Expert Panel Report 3 (EPR-3) recommends the use of spirometry in the diagnosis and periodic monitoring of patients with asthma [11]. The use of symptoms alone has been shown to underrepresent the degree of asthma severity [26]. Symptoms are fairly reliable indexes of asthma control; however, symptoms and lung function do not always correlate.…”
Section: Discussionmentioning
confidence: 99%
“…The GINA classification is perhaps the most widely recognised and recommended asthma assessment tool worldwide [ 11 ]. Although the GINA classification has not been formally validated, recent studies have demonstrated different degrees of agreement between it and other tools [ 24 - 26 ]. When Rodrigo et al [ 25 ] tested the Spanish version of the ACT, they observed that the instrument had a weak correlation with FEV 1 and that almost 40% of patients with a predicted FEV 1 less than 60% had considered his illness totally controlled, concluding that the ACT is not an appropriate tool to guide asthma management if used without spirometry.…”
Section: Discussionmentioning
confidence: 99%